Melampaui Akal dan Indera: Rekonstruksi Epistemologi Al-Ghazālī Berbasis Qalbu dan Relevansinya bagi Pendidikan Islam Kontemporer - Muhammad Sholeh Afif; Triyo Supriyatno (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Contemporary Islamic education in Indonesia faces a critical juncture between technological opportunities and epistemological crises. The massive expansion of digital access has intensified the dominance of sensory knowledge (ilmu ḥissiyah) and rational-instrumental knowledge (ilmu ʿaqliyah), while marginalizing the spiritual-moral dimension centered on the qalbu. This condition is empirically reflected in the rising prevalence of emotional disorders among adolescents, spiritual emptiness, existential crises, and psychological pressure exacerbated by digital culture and the shift to online learning during the COVID-19 pandemic. Over-reliance on sensory and technological approaches without strengthening the qalbu has resulted in psychospiritual dysfunction among learners. In this context, Al-Ghazālī's epistemology offers a relevant critique and reconstruction. Through his works such as al-Munqiḍ min al-Ḍalāl and Iḥyāʾ ‘Ulūm al-Dīn, Al-Ghazālī constructs a hierarchical and integrative epistemological framework, placing sensory and rational knowledge under the leadership of a purified qalbu that receives divine illumination (ilm ladunī). The qalbu functions as the "king" integrating all human faculties, ensuring knowledge is not merely cognitive but transformative, ethical, and oriented toward maʿrifatullāh within the framework of tawḥīd. This study employs a qualitative approach with library research and philosophical-conceptual analysis to reconstruct Al-Ghazālī's qalbu-centric epistemology and elaborate its implications for contemporary Islamic education. The reconstruction affirms the hierarchical structure: sensory knowledge as the base, rational as intermediate, and qalbu illumination as the peak through tazkiyat al-nafs. Practical implications include developing a holistic Islamic education model that integrates tazkiyah practices into the PAI curriculum, learning strategies based on adab, muraqabah, and muḥāsabah, as well as harmonizing digital technology with spiritual formation. This approach is expected to overcome spiritual emptiness, stabilize learners' psyche, form noble character, and renew PAI curriculum toward a tawḥīd-oriented, transformative education in the digital era. Keywords: Al-Ghazali Epistemology, Qalb, Islamic Education, Soul Purification, Contemporary Education